Sistem Portable Hybrid On-Grid PV-PLN-Generator Teraplikasi Di Desa Pemulutan - Pradana, Wirawan Adi; Sofijan, Armin; Cekdin, Cekmas; Bizzy, Irwin (JURNAL SURYA ENERGY, 2022)
Pemulutan village has a location that is separated by a small river, where only one of its locations has access to PLN electricity rom the government. The portable hybrid on grid system PV-PLN-Generator has the ability to combine a power source from PLN with alternative sources of electricity from solar panels and generators, this system was applied in this study by adding a portable system, so that it can be carried and moved easily from opposite locations of river. The ouput power of one solar panel is about 20-25 W, so it takes 6-7 solar panels to be used with load 70 Watt for 12 hours. The results of this research are very helpful for Pemulutan’s village, with the portable hybrid on grid (PHoG) system can help access electricity for lighting, process garden products, and relieve the cost of charging PLN electricity.